2021
DOI: 10.1080/27658511.2021.1901389
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of water supply system from catchment to consumers as framed in WHO water safety plans: A study from Maiduguri water treatment plant, North East Nigeria

Abstract: Water safety plan (WSP) concept of World Health Organisation based on risk management from catchment to consumers ensures safe drinking water supply by water supply utilities. Water supply system assessment is integral to effective WSP development and implementation. This study reports assessment of Maiduguri water treatment plant from catchment to consumers, toward providing baseline information for effective WSP. A cross-sectional study involving questionnaire, key informant interview, and water analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…In the present study, all the physico-chemical parameters explored were in consonance with the optimum range for survival and growth of fish 13,15 , except few parameters including dissolved oxygen, alkalinity, conductivity, hardness and calcium. This observation corroborates the previous report by Mustapha et al 16 , who investigate the the water supply system from Maiduguri water treatment plant. These authors found similar temperature, pH, sodium, potassium and magnesium range values that fell within the standard recommended range for aquaculture.…”
Section: Physico-chemical Parameterssupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, all the physico-chemical parameters explored were in consonance with the optimum range for survival and growth of fish 13,15 , except few parameters including dissolved oxygen, alkalinity, conductivity, hardness and calcium. This observation corroborates the previous report by Mustapha et al 16 , who investigate the the water supply system from Maiduguri water treatment plant. These authors found similar temperature, pH, sodium, potassium and magnesium range values that fell within the standard recommended range for aquaculture.…”
Section: Physico-chemical Parameterssupporting
confidence: 93%
“…Similar to this study, Mustapha et al 16 and Hyeladi and Nwagilari 9 found the total hardness groundwater boreholes in Maiduguri to be less than 50 CaCO 3 mg LG 1 and classified as soft water based on the classification of Hori et al 17 . Jimme et al 8 , however, reported that deep and wash boreholes in Maiduguri based on total hardness varied from slightly hard (105.0 mg LG 1 ) to very hard (519.0 mg LG 1 ) as classified by Hori et al 17 .…”
Section: Physico-chemical Parameterssupporting
confidence: 83%
“…The data, extracted in CSV and RIS formats, undergoes processing through VOSviewer. The article search is confined to the previously identified keywords, and database searches are restricted to the timeframe from 2020 to 2022, resulting in the retrieval of 284 articles (Mustapha et al, 2021).…”
Section: Initial Search Resultsmentioning
confidence: 99%
“…Isfahan's drinking water supply system in Iran as a pilot in 2011 implemented a water safety plan (14). The main aim of WSP is to prevent contamination of raw water sources, to eliminate water contamination by treatment, and to prevent secondary contamination during storage, distribution, and use (16)(17)(18)(19). That is the reason for the superiority of this plan over traditional methods of water quality assessment.…”
Section: Introductionmentioning
confidence: 99%